2021
DOI: 10.1080/23748834.2021.1978786
|View full text |Cite
|
Sign up to set email alerts
|

Walking as urban communication: affordances and agency in public space in a semi-lockdown city

Abstract: While unlimited pedestrian mobility is usually considered a key characteristic of open democracies and healthy urban communication, a global pandemic has re-organised how public space can be used. By analysing places of interaction, infrastructure, and politics and civil society, this article examines walking in the pandemic city as a form of urban communication. The article explores meanings that young adults give to walking in semi-lockdown Helsinki, Finland by employing a qualitative multi-method approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Many studies also focused on the increased interest in cycling. Debates about creating urban infrastructures more suitable for pedestrian and cycling mobility were prompted by the growth in walking and bike usage for leisure and also as a commuting mode, and those debates have included renewed attention on bike‐sharing schemes (de Séjournet et al, 2022; Lukić et al, 2022; Niitamo, 2021; Nikiforiadis et al, 2022; Strömberg & Wallgren, 2022; Teixeira et al, 2021). Attention to other modes of micromobility (Li et al, 2021) also found informed city‐wide and neighbourhood policies concerned with long‐term planning for and design and management of urban green mobility infrastructure using pedestrianisation of public spaces, pedestrian‐friendly walking infrastructure, bike paths, and other cycling infrastructure (Fenu, 2021; Nikiforiadis et al, 2022; Ugolini et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies also focused on the increased interest in cycling. Debates about creating urban infrastructures more suitable for pedestrian and cycling mobility were prompted by the growth in walking and bike usage for leisure and also as a commuting mode, and those debates have included renewed attention on bike‐sharing schemes (de Séjournet et al, 2022; Lukić et al, 2022; Niitamo, 2021; Nikiforiadis et al, 2022; Strömberg & Wallgren, 2022; Teixeira et al, 2021). Attention to other modes of micromobility (Li et al, 2021) also found informed city‐wide and neighbourhood policies concerned with long‐term planning for and design and management of urban green mobility infrastructure using pedestrianisation of public spaces, pedestrian‐friendly walking infrastructure, bike paths, and other cycling infrastructure (Fenu, 2021; Nikiforiadis et al, 2022; Ugolini et al, 2021).…”
Section: Resultsmentioning
confidence: 99%